Impak Pentaksiran Pendidikan Pintar dan Berbakat Integrasi Naqli dan Aqli (IGEd) - Nurhidaya Mohamad Jan; Hatika Kaco; Fadzidah Mohd Idris; Siti Munirah Mohd (Penerbit UTM Press, 2024)
Vol. 7 No. 1 (Page: 75–89)